Implementasi Kegiatan Ektstrakurikuler PAI (Ikhrohist) untuk Pembinaan Akhlak - Sudiran Sudiran (Institut Agama Islam Negeri Palopo, 2019)
This researh is about the implementation of extracurricular activities (ikrohist) for guide students’ attitude in SMK Penerbangan Techno Terapan Makassar. This research method is a qualitative research using of normative theology, pedagogic, physicologic, and sociologic. The research instruments used interview, observation, and documentation. Informant consisted of principal, refresentative of the school, and teachers. Data collection was done by observation, interview and documentation techniques. Data analysis by means of data reduction, data presentation, conclusion and data verification. The result of this research, there are: 1) Students’ attitudes in SMK Penerbangan Techno Terapan Makassar, after joining the extracurricular activities showed good attitudes. 2) Students’ Attitudes in SMK Penerbangan Techno Terapan Makassar based on the observation and interview that give awardness, discipline, extracurricular activities (Ikrohist) in SMK Penerbangan Techno Terapan Makassar consisted of three parts, they are dayly/weekly activities, monthly activities and annual activities.